The Role of Internet of Things (IoT) for Life : An Overview - Akhmad Wijaya Kusuma (Peneliti.net, 2022)
This paper discusses the role of IoT in human life. The benefits of IoT are to lighten the workload and increase the effectiveness of a tool. This paper uses the literature review method derived from articles and books. Articles that focus on IoT will be clearly reviewed. There are 4 articles to be reviewed. 1 international article and 3 national articles. It's time for IoT to be used for developing countries. The use of IoT will improve the quality of life. There are limitless benefits for IoT applications in every way. The Internet of Things holds important promise to provide social and economic benefits for growing and developing economies. This includes areas such as home electronics, water quality and use and health care